2016
DOI: 10.1159/000446297
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic Evolution in Malagasy Flying Foxes (Pteropodidae, Chiroptera) and Their Hipposiderid Relatives as Determined by Comparative Chromosome Painting

Abstract: Pteropodidae and Hipposideridae are 2 of the 9 chiropteran families that occur on Madagascar. Despite major advancements in the systematic study of the island's bat fauna, few karyotypic data exist for endemic species. We utilized G- and C-banding in combination with chromosome painting with Myotismyotis probes to establish a genome-wide homology among Malagasy species belonging to the families Pteropodidae (Pteropus rufus 2n = 38; Rousettus madagascariensis, 2n = 36), Hipposideridae (Hipposideros commersoni s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In total, 13 species have been studied with G-banding. FISH analyses were undertaken for 5 species from 4 genera (2n in parentheses), i.e., Cynopterus (34), Eonycteris (36), Rousettus (36), and Pteropus (38) [ 62 , 68 , 74 , 75 , 97 ].…”
Section: Overview Of Chromosomal Evolution Within Chiropteran Famimentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 13 species have been studied with G-banding. FISH analyses were undertaken for 5 species from 4 genera (2n in parentheses), i.e., Cynopterus (34), Eonycteris (36), Rousettus (36), and Pteropus (38) [ 62 , 68 , 74 , 75 , 97 ].…”
Section: Overview Of Chromosomal Evolution Within Chiropteran Famimentioning
confidence: 99%
“…However, detailed morphological studies [ 111 ] and DNA sequence analyses revealed that both genera are in fact distantly related [ 3 ]. In contrast, the molecular hypothesis of a close relationship between Eonycteris and Rousettus (subfamily Rousettinae) is also supported by karyotype similarities [ 97 ]. The karyotype of M. sobrinus , based on the analysis of one male and one female from Peninsular Malaysia (Ulu Gombak, Selangor), consists of 2n = 34 and FN = 60.…”
Section: Overview Of Chromosomal Evolution Within Chiropteran Famimentioning
confidence: 99%
See 3 more Smart Citations